A new sustainable formulated feed based on discards from food industries for rearing the sea urchin Paracentrotus lividus (Lmk). (22nd February 2019) - Vizzini, Salvatrice; Visconti, Giulia; Signa, Geraldina; Romano, Salvatore; Mazzola, Antonio
Abstract: During a 18‐week experiment in a sea‐based system, Paracentrotus lividus was fed with two formulations of a new sustainable feed whose main ingredients were food farming discards, mostly outermost lettuce leaves, in different percentage. Egg white was added as protein source and binder, and a little amount of commercial fish feed was added as lipid source. At the end of the experiment, a high survival rate (>80%) and an increase in test diameter (22%), total weight (130%), gonad weight (240%) and gonad index expressed as size‐adjusted gonad weight (288%) were recorded. Gonads achieved a good colour and high levels of essential and polyunsaturated fatty acids, hence representing a commercially valuable product. Comparing the two feed formulations, the one with the lower lettuce content (57% vs. 67%) led to the best product quality, in terms of gonad features (gonad index and colour) and content of essential fatty acids. In order to move towards a higher sustainability of the aquaculture sector, this study proposes a low‐cost feed, produced with cheap and sustainable ingredients such as food farming discards.